Study the Duration of Steam Power Plant’s Maintenance to Improve the Equivalent Availability Factor - Purjanto, Dody Awin; Santosa, Budi (IPTEK Journal of Proceedings Series, 2019)
Periodic maintenance of power plants is included in the project. Shorter project duration than scheduled indicates the success of the project. For the electricity industry, operating earlier will increase the availability index, which in turn will increase revenue. The standard maintenance work scope of the power plant owner is presented in a detailed work structure of the project as known as Work Breakdown Structure (WBS). Project scheduling is done using network technique with the Critical Path Method (CPM). All activities that are on the critical path can be done crashing to speed up work in shortening the duration of treatment. Crashing is done by utilizing the cost slope of critical activities. So information can be obtained about the costs of several possible durations. The study of power plant maintenance using a cost slope gets an accelerated duration with the smallest cost, which is 28 days. With a maintenance duration of 28 days the total cost is 3,854,670,611 rupiahs and with an additional income of 429,643,368 rupiah from normal income of 21,404,712,886 rupiahs